PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN TEORI BELAJAR BRUNER PADA SISWA KELAS VIII - Melly Afrida Handayani, Yurnalis (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Based on the results of author interviews with teachers of mathematics in MTsN Paninjauanobtained information on the results of student learning is still low, students are not the focus ofthe learning process, students' difficulties in understanding the material provided by theteacher, the teacher gives direct mathematical concept, so that students can develop theircreativity to find their own the mathematical concepts and students participate less active anddo not want to ask in the learning process. Formulation of the problem in this research is: Howis student learning outcomes in the affective, How are student learning outcomes inpsychomotor and Is student learning outcomes in the cognitive domain by applying Modeldiscovery using learning theory of Bruner is better than the student learning outcomes in thecognitive domain without applying the discovery model using learning theory of Bruner inclass VIII MTsN Paninjanuan. The population in this study were students of class VIII MTsNPaninjanuan. Samples are VIII.B graders and graders VIII.C MTsN Paninjauan. The researchwas Rondomized Only Control Group Design. The sampling technique is random sampling.The statistical test used was the t test 'to test the hypothesis, derived, it can be concluded that the results of students'mathematics learning class VIIIC MTsN Paninjauan by applying the model of discoverylearning in mathematics learning using learning theory of Bruner in the eighth grade studentsMTsN Paninjauan better than those not using it in math class VIII MTsN Paninjauan.